2011
DOI: 10.1073/pnas.1010529108
|View full text |Cite
|
Sign up to set email alerts
|

Normal gut microbiota modulates brain development and behavior

Abstract: Microbial colonization of mammals is an evolution-driven process that modulate host physiology, many of which are associated with immunity and nutrient intake. Here, we report that colonization by gut microbiota impacts mammalian brain development and subsequent adult behavior. Using measures of motor activity and anxiety-like behavior, we demonstrate that germ free (GF) mice display increased motor activity and reduced anxiety, compared with specific pathogen free (SPF) mice with a normal gut microbiota. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

49
2,264
6
42

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,752 publications
(2,361 citation statements)
references
References 42 publications
49
2,264
6
42
Order By: Relevance
“…The hypothalamus and the brain stem are central sites of appetite regulation 11. The gut microbiome can stimulate vagal sensory neurons, which is a major neural pathway that conveys information from the gastrointestinal luminal contents to the brain and modulates gastrointestinal motility and feeding behavior 12, 13. The gut microbiome can influence neuronal signaling to the brain through vagal afferent neurons 14.…”
mentioning
confidence: 99%
“…The hypothalamus and the brain stem are central sites of appetite regulation 11. The gut microbiome can stimulate vagal sensory neurons, which is a major neural pathway that conveys information from the gastrointestinal luminal contents to the brain and modulates gastrointestinal motility and feeding behavior 12, 13. The gut microbiome can influence neuronal signaling to the brain through vagal afferent neurons 14.…”
mentioning
confidence: 99%
“…Recently, the studies illustrated the relevance of a striatum, which proved their hypothesis that the "healthy" gut microbiota is an integral part of the external environmental signals that modulate brain development and function (Heijtz et al, 2011). However, once the gut microbiota community is interrupted by multiple factors including maternal vertical transmission, genetic makeup of the individual, diet, medications such as antibiotics, GI infections and stress, the gut homeostasis is subsequently imbalanced and causes detrimental effects on CNS through gut-brain axis (Heijtz et al, 2011), while some other experiments concluded that the gut microbiota infl uence brain chemistry and behavior independently of the autonomic nervous system, GI-specifi c neurotransmitters, or infl ammation .…”
Section: The Gut-brain-liver Axismentioning
confidence: 99%
“…GF mice displayed increased motor activity and reduced anxiety, compared with SPF mice with normal gut microbiota (Heijtz et al, 2011). However, there needs to be additional studies required in analyzing the direct role of the gut microbiota influencing the gut-brain axis.…”
Section: Review Protein Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…L'impact du microbiote intestinal n'est pas limité à l'intestin, il s'exerce également à l'échelle systémique des organismes hôtes. Il régule en effet la maturation du système immunitaire [5,6], la croissance post-natale [7,8], et peut même influencer l'activité cérébrale [9,10,48] (➜). Chez l'homme, des perturbations du microbiote intestinal sont associées à une grande variété de pathologies d'ordre métabolique, immunitaire ou même cognitif [11,12].…”
unclassified